2017
DOI: 10.31142/ijtsrd2509
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water Quality Using Physico-chemical Parameters of Mula-Mutha River, Pune Maharashtra

Abstract: We want to present an extensive work on physico chemical parameters of water samples of Mula river at Pune (Maharashtra). Water samples under investigations were collected from Khadkwasla dam to Sangam Bridge during pre monsoon (April May2016) monsoon (July-August2016) and post monsoon (October-November2016) seasons. The observed values of different physico parameters like pH, DO, BOD, COD, Chloride, Nitrate, Sulphate, Calcium, Magnesium and Hardness, etc. of samples were compared with standard values recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The present observation finds support with the work of Akumtoshi et al, 2020 in Doyang River, Nagaland. The raised values of D.O during winter season in Site I were due to high photosynthetic rate by phytoplankton during which more CO 2 is utilised and O 2 is released (Jadhav and Jadhav, 2018). The DO level in our study site was found to be higher than the acceptable limits of 5 mg -1 (BIS, 2003).…”
Section: Data Of Water Qualitymentioning
confidence: 55%
“…The present observation finds support with the work of Akumtoshi et al, 2020 in Doyang River, Nagaland. The raised values of D.O during winter season in Site I were due to high photosynthetic rate by phytoplankton during which more CO 2 is utilised and O 2 is released (Jadhav and Jadhav, 2018). The DO level in our study site was found to be higher than the acceptable limits of 5 mg -1 (BIS, 2003).…”
Section: Data Of Water Qualitymentioning
confidence: 55%
“…Vermicompost application 2.5 t ha -1 increased gram and straw yield of rice significantly and saved up to 50% of recommended NPK fertilizer rates in upland rice (Angadi and Radder, 1996). Earthworms' cast (vermicompost) found to be a better source for enhanced plant growth, dry matter production, productivity and also indicated the possibility of substituting 50 kg N ha -1 from the recommended dose of N (Jadhav et al, 1997)). Thus, vermicompost usage reduced dependence on costly fertilizer input and enhanced net returns from rice produce (Nagaranjan, 1997).…”
Section: Nagavallemmamentioning
confidence: 99%
“…Water is the most vital resource required for survival of life forms on earth Mishra et al 2020;Jadhav et al 2020). The freshwater bodies play an integral role in ful lling water demands in industrial, domestic and farming purposes Cahyanto et al 2019;Nguyen etal.2019).…”
Section: Introductionmentioning
confidence: 99%